Regulation of Gastrointestinal Motility by Motilin and Ghrelin in Vertebrates - Kitazawa, Takio; Kaiya, Hiroyuki (Frontiers in Endocrinology, 2019)
The energy balance of vertebrates is regulated by the difference in energy input and energy expenditure. Generally, most vertebrates obtain their energy from nutrients of foods through the gastrointestinal (GI) tract. Therefore, food intake and following food digestion including motility of the GI tract, secretion and absorption are crucial physiological events for energy homeostasis. GI motility changes depending on feeding, and GI motility is divided into fasting and postprandial contraction patterns. GI motility is controlled by contraction of smooth muscles of the GI tract, enteric and intrinsic neurons (motor and sensory) and some hormones. In mammals, ghrelin (GHRL) and motilin (MLN) stimulate appetite and GI motility and contribute to the regulation of energy homeostasis. GHRL and MLN are produced in the mucosal layer of the stomach and upper small intestine, respectively. GHRL is a multifunctional peptide and is involved in glucose metabolism, endocrine/exocrine functions, and cardiovascular and reproductive functions in addition to feeding and GI motility in mammals. On the hand, the action of MLN is restricted, and species such as rodentia including mice and rats lack MLN peptide and its receptor. From a phylogenetic point of view, GHRL and its receptor GHS-R1a have been identified in various vertebrates, and their structural features and various physiological functions have been revealed. On the other hand, MLN or MLN-like peptide (MLN-LP) and its receptors have been found only in some fish, birds and mammals. Here, we review the actions of GHRL and MLN with focus on contractility of the GI tract of species from fish to mammals.